Methods of testing refractory materials Part 3. General and textural properties Section 3.13 Measurement of corner and edge defects and other surface imperfections of refractory bricks and blocks ( attributive properties ) ( method 1902-313 ) (BSI, 1985)
Refractories, Refractory materials, Defects, Flaws, Surface defects, Surface properties, Indentations, Physical properties of materials, Physical property measurement, Protuberances, Dimensional measurement, Linear measurement, Accuracy, Mechanical measurement, Measurement